(untitled) (E Global Congress, 2025)
This article explores the evolving role of educators in the context of health-preserving pedagogy, presenting teacher competence as a multidimensional and dynamic phenomenon. Moving beyond conventional definitions, the discussion emphasizes how pedagogical competence must be reimagined in light of contemporary educational demands, technological integration, and students’ psychosocial needs. The paper advocates for a holistic approach that positions the educator not only as a disseminator of health knowledge, but as a facilitator of sustainable behavioral change, ethical awareness, and lifelong wellness habits. Through this lens, the article offers a conceptual foundation for developing professional development programs and institutional policies that can strengthen the impact of health-focused educational strategies. By reframing the educator’s function as both a role model and a transformative guide, the study opens avenues for more inclusive, reflective, and future-oriented teaching practices within higher education systems.